Impact of E-vapor aerosols on the cardiovascular and respiratory systems in ApoE−/− mice - Justyna Szostak; Ee Tsin Wong; Bjoern Titz; Tom Lee; Sin Kei Wong; Tiffany Low; Kyonghee Monica Lee; Jingjie Zhang; Ashutosh Kumar; Walter K. Schlage; Emmanuel Guedj; Blaine Phillips; et al. (INTERVALS, 2020)
This study aims to investigate the impact of exposure to e-vapor aerosols on the cardiovascular and respiratory systems. The assessment was performed over a 6-month period on ApoE−/− female mice. Three different E-vapor formulations (carrier (propylene glycol and vegetable glycerol), base (carrier and nicotine) and test (base and flavor)) were tested and compared with the impact of exposure to the mainstream smoke of cigarettes.
Classical endpoints were first explored: biomarkers of exposure, hematological and lipidic parameters, as well as oxidative stress and inflammation, were investigated following exposure.
The cardiovascular system was then explored and atherosclerosis, histopathological alterations, transcriptomics analysis, and functional modifications were investigated.
Finally, at the respiratory system level, inflammation, histopathological alterations, multi-omics analysis, DNA methylation, and functional changes were explored.
Keywords: In vivo; Aerosol; Mouse; DNA methylation; Plaque formation; Respiratory physiology (lung function); Organ weight; Lipidomics; Body weight; Cell count; Proteomics; Histopathology; Transcriptomics; Food and water consumption; Analytical chemistry; Aerosol physical measurement; Carboxyhemoglobin; Aerosol composition; Biomarkers of exposure; BALF Free lung cells; Statistical analysis; In life observation; CT scan; Organ volume; Electrocardiogram (ECG); Clinical chemistry; Echography; 3R4F; TestMix (MarkTen, Altria); Base (MarkTen, Altria); Carrier (MarkTen, Altria); Urine; Heart; Aorta; Nose; Liver; Whole body; Bronchoalveolar lavage fluid - BALF; Lung; Blood; Kidney; Larynx; Spleen; Thymus; Trachea; Uterus; Whole aerosol; Thyroid; Brain; Bone; Ovary; Adrenal gland; Adverse events; Respiratory disease; Cardiovascular disease; Liver diseases; Exposure characterization; Exposure markers; Xenobiotic metabolism; Cellular and tissue damage; Inflammation; Oxidative stress